Comparative analysis of three histologic grading methods for squamous cell carcinoma of the lip - Strieder, L. [UNESP]; Coutinho-Camillo, C. M.; Costa, V. [UNESP]; da Cruz Perez, D. E.; Kowalski, L. P.; Kaminagakura, E. [UNESP] (Wiley, 2017)
Objectives: The aim of this study was to evaluate three histologic grading methods for squamous cell carcinoma (SCC) of the lip, the conventional three-grade model proposed by the World Health Organization, tumor budding and depth of invasion (BD) model, and histologic risk assessment (HRA) model, and to correlate them with prognosis. Materials and Methods: Fifty-three patients with lip SCC were evaluated. Results: The mean age was 65 years, 69.8% of the participants were men, and 66.0% of the patients had early-stage tumors. Using the BD and conventional three-grade methods, 52.8% and 64.2% of the cases were graded as low risk, respectively. The HRA model graded 54.7% of the cases as medium risk. In the BD model, the higher histologic grade was associated with worse prognosis (P = 0.045). Overall survival at 5 years was 87.8%. Tumor size (T3 + T4) and lymph node involvement (N+) were associated with reduced overall survival and recurrence-free survival (RFS) (P = 0.002 and 0.005; 0.007 and 0.01, respectively). Surgical treatment combined with radiotherapy was associated with lower RFS (P = 0.03). Conclusions: High-grade lip SCC in advanced stages is associated with a poor prognosis. The BD model is a simple and effective tool for the prognostic evaluation of lip SCC.
Keywords: histologic grade; lip squamous cell carcinoma; prognosis; survival analysis